Do we need to vaccinate every child against coronavirus disease 2019 in India? - Suraj Kapoor (Wolters Kluwer Medknow Publications, 2022)
There has been a lot of debate around the coronavirus disease 2019 (COVID-19) vaccination of children throughout the globe, particularly with many seeing it as a prerequisite for the reopening of schools. Secondary data from government official sites, press information, latest articles, and newspapers were extracted and discussed in the article. Published literature in respect of COVID-19 vaccination in children reveals that the transmission of COVID-19 is much lesser by the children, with milder course especially among younger children. Further, the risk of transmission by the young children seems very less especially with the recent variant of concern, omicron, in which majority of the infected (80%) remain asymptomatic. Hence, the policymakers need to prioritize the pediatric beneficiary for the vaccination. Age-specific morbidity and mortality trends of the country as well as across the different countries may help in deciding the groups within the pediatric population requiring urgent vaccination. Reports suggests that the pediatric population benefitting the most will be the children with underlying comorbidities or medical condition like malignancy, heart diseases, lifestyle diseases including childhood diabetes, obesity, and hypertension, and renal abnormalities. Since the safety and effectiveness of recently launched COVID-19 vaccines needs exploration in pediatric age group, it may be prudent to have pediatric vaccination among the specific groups who are at higher risk of contracting the severe disease rather than going for mass vaccination drive.